2018
DOI: 10.1111/andr.12513
|View full text |Cite
|
Sign up to set email alerts
|

Association between leukocytospermia and semen interleukin‐6 and tumor necrosis factor‐alpha in infertile men

Abstract: Seminal cytokines were previously reported to adversely affect process of spermatogenesis and ultimately induce poor semen quality. However, association between both IL-6 and TNF-α and leukocytospermia was not yet settled. The aim of this study was to evaluate the association between leukocytospermia and levels of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) in semen of infertile men. This cross-sectional study included 100 age-matched (≥18-45 years.) men. Participants were divided into four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
(46 reference statements)
5
24
0
1
Order By: Relevance
“…Second, patients with adenomyosis had higher levels of IL-6, IL-8, TNF-a, and reactive oxygen species in the peritoneal fluid. These high levels of immune-inflammatory cytokines might result in ovarian dysfunction and impaired sperm quality, causing infertility [21][22][23][24]. Furthermore, women with adenomyosis have a low expression of progesterone receptors, which are required for uterine receptivity [3].…”
Section: Discussionmentioning
confidence: 99%
“…Second, patients with adenomyosis had higher levels of IL-6, IL-8, TNF-a, and reactive oxygen species in the peritoneal fluid. These high levels of immune-inflammatory cytokines might result in ovarian dysfunction and impaired sperm quality, causing infertility [21][22][23][24]. Furthermore, women with adenomyosis have a low expression of progesterone receptors, which are required for uterine receptivity [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the process of spermatogenesis, reactive oxygen species are very harmful, and the content of unsaturated fatty acids in sperm membrane is easily affected by oxidative stress, and these lipids can be oxidized through a series of chain reactions to release potential toxicity and mutagenic aldehydes and alkenals [34][35][36], nally, excessive ROS has a pathological impact on spermatogenesis, resulting in the decrease of sperm concentration, motility and fertilization rate [37]. A large number of clinical studies have shown that leukocytospermia-induced sperm damage may be due to high levels of leukocyte-derived ROS and in ammatory mediators, Such as toll-like receptors 2 and 4 (TLR-2/4), cyclooxygenase-2 (COX-2), nuclear factor erythryoid-2 related factor (Nrf-2), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), etc [38,39], even low levels of leukocytospermia have seminal oxidative stress [40]. It is not certain that the effect of leukocytospermia or UU infection on sperm exists, but it seems to be explainable from the current mechanism research.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of spermatogenesis, reactive oxygen species are very harmful, and the content of unsaturated fatty acids in sperm membrane is easily affected by oxidative stress, and these lipids can be oxidized through a series of chain reactions to release potential toxicity and mutagenic aldehydes and alkenals [34][35][36], nally, excessive ROS has a pathological impact on spermatogenesis, resulting in the decrease of sperm concentration, motility and fertilization rate [37]. A large number of clinical studies have shown that leukocytospermiainduced sperm damage may be due to high levels of leukocyte-derived ROS and in ammatory mediators, Such as toll-like receptors 2 and 4 (TLR-2/4), cyclooxygenase-2 (COX-2), nuclear factor erythryoid-2 related factor (Nrf-2), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), etc [38,39], even low levels of leukocytospermia have seminal oxidative stress [40]. It is not certain that the effect of leukocytospermia or UU infection on sperm exists, but it seems to be explainable from the current mechanism research.…”
Section: Discussionmentioning
confidence: 99%